The Model of Arabic Learning Translation Using Artificial Intelligence in Social-Media - Abd. Rozak; Kisno Umbar; Azkia Muharom Albantani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This research is aimed at revealing the existence of new alternatives in translation teaching media. Translation teaching media is still strongly suspected to be dominated by the use of dictionaries, both in print such as Munawir, Munjid, Mahmud Yunus, and digital dictionaries like al-Maany, Google Translate, and other applications. The alternative media offered is social media such as Twitter (X). Social media usually used in public communication can be utilized as an alternative for translation learning. How to utilize social media such as Twitter in translation learning? How accurate is social media in teaching Arabic-Indonesian or Indonesian-Arabic translation? This research falls under the category of qualitative research when viewed from the source of text data used. The method used in the research is descriptive qualitative method. The researcher will systematically present examples of using social media (Twitter) in translation learning. The data source in this study is tweets in Arabic language on Twitter. The results of this study indicate that Twitter can be an alternative translation teaching media. The auto-translate system available on Twitter provides several advantages in translation teaching, such as access to authentic and contemporary materials, development of translation speed and accuracy, exercise in finding equivalent words that are currently trending in the Arab world. However, the translations displayed by the auto-translate system on Twitter still need to be considered because there are various contexts that machine translators cannot read.